Potential Risk Factors for Childhood Overweight and Obesity Among WIC Participating Preschool Children - Charvet, Andrea (Curr Dev Nutr, 2021)
OBJECTIVES: To identify risk factors associated with the risk for overweight/obesity in preschool children ages 3 up to 5 years participating in the Broward County Special Supplementation Nutrition Program for Women, Infants, and Children (WIC). METHODS: Cross-sectional data were collected from all 7 Broward County Health Department WIC clinics over 4 months via a researcher-administered questionnaire. Additional data were extracted from the WIC data system. Children were classified into weight categories following the CDC's BMI-for-age percentiles, which were further combined into under/normal weight and overweight/obese. RESULTS: A total of 197 participants [90 boys (45.7%) and 107 girls (54.3%)] were included. From those, 68% were overweight/obese and 32% under/normal weight. Sugar sweetened beverage (SSB) intake was significantly greater in the overweight/obese group (7.45 ± 8.71 vs. 4.60 ± 6.64 oz/d, P = 0.024). Fruits were consumed daily by 67% of the children, and vegetables by 35%, with no significant association with weight category. Breakfast was skipped at least once/week by 16.5% of the children, independent of body weight. On average, children had 2.3 h/d of screen time and were physically active for 37.9 min/d. While screen time was not significantly different by weight category, children in the under/normal weight group were significantly more physically active when compared to their counterparts (41.9 ± 29.3 vs. 29.3 ± 27.0 min/d, P = 0.004). Only 15.2% of parents/guardians of overweight and 43.3% of obese children identified their child as being too big. Mean birth weight for overweight/obese children was significantly higher (7.41 ± 1.12 vs. 7.04 ± 1.17 lbs, P = 0.038). On a logistic regression model, SSB intake, physical activity, and birth weight were significant predictors of overweight/obesity. CONCLUSIONS: Physical activity was negatively correlated with the risk of overweight/obesity, while the intake of SSB and birth weight were positively correlated. In addition, most participants failed to perceive their overweight/obese child as such. This study points out important factors to be considered in obesity prevention interventions in this population. FUNDING SOURCES: AC was supported by a NIH/NIGMS R25 grant. The FIU Dietetics and Nutrition research foundation supported the study.